PHARMACOGNOSTIC EVALUATION AND PRELIMINARY PHYTOCHEMICAL SCREENING OF CORDIA DICHOTOMA FORST FRUITS. - SUMIT R DEORE; AJAY G NAMDEO (International Journal of Pharma and Bio Sciences, 2013)
The present communication deals with the pharmacognostical and preliminary phytochemical studies on the fruits of Cordia dichotoma Forst. Very less reports are available on pharmacognostic and phytochemical studies, hence, the present study was undertaken to investigate the same. All the parameters were studied regarding the WHO and pharmacopoeial guidelines. Ash values, extractive values in different solvents, fluorescence analysis, treatment with different reagents and phytochemical screening have been carried out. The study will be useful for the identification of fruit of Cordia dichotoma and will prevent its adulteration.